Accessing higher education in developing countries: Panel data analysis from India, Peru, and Vietnam - Sánchez, A; Singh, A (Young Lives, 2016)
We use unique individual-level panel data from India (Andhra Pradesh), Peru, and Vietnam on a cohort of individuals surveyed from the age of 8 years to 19 years to study factors affecting enrolment in higher-education in these middle-income countries. We document (a) that similar to nationally representative data, the proportion having accessed higher-education at this age is high (~35-45 per cent); (b) that there are steep gradients in higher-education access across wealth and parental education; (c) that a substantial part of the gradient with regard to parental education is explained by parental and child aspirations for education, at 12 years of age, and previous measures of learning; (d) that in contrast, wealth gradients decline much less with the inclusion of these variables, indicating that the correlation between household economic circumstances and higher-education access is only partly due to differences in early-childhood human-capital formation; and (e) that there are important differences in terms of gender in access to levels of higher-education (favouring boys in India and girls in Vietnam) and in the association of various household and individual characteristics and parental and child aspirations with enrolment in higher-education by 19 years of age. To the best of our knowledge, this is the first such comparative longitudinal analysis of access to higher-education in developing-country settings.